Unveiling the role of critical thinking in education: regional analysis and predictive factors - Fadillah, Muhammad Aizri; Tanjung, Yul Ifda; Usmeldi, Usmeldi; Festiyed, Festiyed (International Journal of Evaluation and Research in Education (IJERE), 2025)
Despite its recognized importance, the role of critical thinking (CRIT) in promoting authentic problem-solving (APS), collaborative learning (COL), creative thinking (CRET), and knowledge creation efficacy (KCE) in different regional contexts still needs to be investigated. This study uses partial least squares-structural equation modeling (PLS-SEM) and partial least squares-multi group analysis (PLS-MGA) to evaluate the effect of CRIT on these skills and compare the effect between municipality and regency, using data from 431 high school students in Indonesia. The Ranger algorithm identified the main predictors of the impact of CRIT on the other skills. The findings revealed that CRIT significantly improved the impacts of these skills, with no significant differences between regions. The ability to provide sound reasoning and consider diverse perspectives were the main predictors. This study contributes to the relatively under-attended area of CRIT in Indonesian education by highlighting its important role in skills development.